2009
DOI: 10.1007/s12043-009-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of gold cages (Au16 and Au17) at finite temperature

Abstract: We have employed ab initio molecular dynamics to investigate the stability of the smallest gold cages, namely Au16 and Au17, at finite temperatures. First, we obtain the ground state structure along with at least 50 distinct isomers for both the clusters. This is followed by the finite temperature simulations of these clusters. Each cluster is maintained at 12 different temperatures for a time period of at least 150 ps. Thus, the total simulation time is of the order of 2.4 ns for each cluster. We observe that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, very symmetric structures often correspond to particularly stable equilibrium structures and may therefore be associated with larger structural excitation energies and higher melting temperatures than the disordered ones. The variability of the isomer spectrum is thus determinant on the thermodynamic properties 21,26,45 and will be analyzed in the discussion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, very symmetric structures often correspond to particularly stable equilibrium structures and may therefore be associated with larger structural excitation energies and higher melting temperatures than the disordered ones. The variability of the isomer spectrum is thus determinant on the thermodynamic properties 21,26,45 and will be analyzed in the discussion.…”
Section: Resultsmentioning
confidence: 99%
“…We will hereafter focus on gold and silver clusters. Their structural and melting properties have been investigated using various experimental setups 34,40,43,44 and theoretical approaches 19,20,[24][25][26][27][28][28][29][30]33,35,36,41,[45][46][47][48][49] , mostly with empirical potentials. The most stable structures reported for different cluster sizes exhibit either very regular shape (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our literature review, we found only one recent example of a configurational search on a cluster using MD simulations, that of Chandrachud et al (Chandrachud, 2009). These researchers employed VASP to study gold cages using Born-Oppenheimer MD to generate initial configurations.…”
Section: Configurational Search Of Clusters By Molecular Dynamics Simmentioning
confidence: 99%